1995
DOI: 10.1172/jci117909
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor phosphorylation, insulin receptor substrate-1 phosphorylation, and phosphatidylinositol 3-kinase activity are decreased in intact skeletal muscle strips from obese subjects.

Abstract: To determine whether the impaired insulin-stimulated glucose uptake in obese individuals is associated with altered insulin receptor signaling, we measured both glucose uptake and early steps in the insulin action pathway in intact strips of human skeletal muscle. Biopsies of rectus abdominus muscle were taken from eight obese and eight control subjects undergoing elective surgery (body mass index 52.9±3.6 vs 25.7±0.9). Insulin-stimulated 2-deoxyglucose uptake was 53% lower in muscle strips from obese subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

34
334
2
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 479 publications
(375 citation statements)
references
References 64 publications
34
334
2
5
Order By: Relevance
“…The major proteins identified as being differentially expressed in control and low-birthweight muscle were PKCζ, p85α (regulatory subunit of PI 3-kinase), p110β (catalytic subunit of PI 3-kinase) and GLUT4. Similar reductions in the expression of PKCζ [10] and p85 [18] have been observed in the skeletal muscle of diabetic subjects, although in the latter case these subjects were also morbidly obese. There are no reports to date on the expression of p110β in muscle from diabetic patients compared to control subjects.…”
Section: Discussionsupporting
confidence: 69%
“…The major proteins identified as being differentially expressed in control and low-birthweight muscle were PKCζ, p85α (regulatory subunit of PI 3-kinase), p110β (catalytic subunit of PI 3-kinase) and GLUT4. Similar reductions in the expression of PKCζ [10] and p85 [18] have been observed in the skeletal muscle of diabetic subjects, although in the latter case these subjects were also morbidly obese. There are no reports to date on the expression of p110β in muscle from diabetic patients compared to control subjects.…”
Section: Discussionsupporting
confidence: 69%
“…Importantly, these results were strictly donor-specific and correlated with levels of the proteins IGF-1R, InsR and/or IRS-1. It has been shown that IRS-1 and InsR levels vary in different tissues of healthy human individuals [27,28]. Furthermore, we found high variation in IGF-1R levels in monocytes isolated from a randomly chosen group of 16 healthy donors.…”
Section: Discussionsupporting
confidence: 53%
“…This is also confirmed by our data in the FDR subjects who, despite an increased risk for the development of Type II diabetes, displayed no detectable abnormalities. In the context of other studies, where such alterations were partly found, this could indicate that secondary factors like hyperglycaemia [26], increased NEFA concentrations [27] or obesity [23,54] interfere with PI3′-kinase/Akt signalling in overt diabetes. With the present methodology, it cannot be excluded that despite similar overall activity/phosphorylation of the investigated signalling molecules an altered spatial organisation contributed to an altered signalling in FDR and diabetic subjects.…”
Section: Discussionmentioning
confidence: 81%